Penguatan Pengaturan Pelaksanaan Wewenang MPR Melalui Fgd Tim Pakar Di Labuan Bajo - Yohanes Servatius Lon (Unika Santu Paulus Ruteng, 2024)
The “Badan Pengkajian MPR RI” is responsible for examining the state system, including the authority of the MPR. For this task, they require input from experts and academics. This article describes the Community Service activities by the Expert Team from Unika Santu Paulus Ruteng together with Group III of the Badan Pengkajian MPR RI in the framework of drafting an academic paper on the regulation of the implementation of the authority of the MPR RI. Through a focused group discussion (FGD) held in Labuan Bajo on July 11, 2023, the Experts/Academics provided their thoughts to the leaders and Members of the Badan Pengkajian MPR RI, the Secretariat General of the MPR and the Technical Committee, regarding the MPR as a crucial and strategic state institution in maintaining and monitoring the governance of all state institutions based on the pillars of Pancasila, the 1945 Constitution of the Republic of Indonesia, the Unitary State of the Republic of Indonesia, and Bhinneka Tunggal Ika. To support the role of the MPR RI, a new law is needed that regulates and explains the authority of the MPR in establishing the constitution as a constitutional basis for the state and also the authority of the MPR in establishing the GBHN as an operational basis for the nation and state. The law also stipulates the authority of the MPR in providing authentic and authoritative interpretations of the text of the law.